A ball-in-ball type self-powered magnetoelectric inertial sensor for 3D multi-angle motion monitoring of humanoid robots. (July 2021) - Wu, Zhenhua; Ai, Jingwei; Huang, Jianyu; Du, Zhuolin; Su, Bin
Abstract: Motion monitoring stands as a powerful tool for humanoid robots to well adapt to nearby changing environment. However, despite the recent advance of inertial measuring units, both simplification of the sensors and free of power supply for 3D multi-angle monitoring remains elusive. Herein we demonstrate a facile & self-powered magnetoelectric inertial sensor for 3D multi-angle head motion monitoring of humanoid robots. A magnetic sphere could freely roll inside a smooth polymeric shell patterned with regionally distributed coils, allowing for monitoring the accelerations for 8 directions in the horizontal plane, the bowing angle for diverse directions in 3D space and rotations when tilting with multi-angle. It can detect an acceleration down to 0.06 m/s 2 and a tilting angle of 2° in the vertical plane. Owing to these sensing capacities, the magnetoelectric inertial sensor can be placed inside a model head for detecting head bowing, head turning and even sudden strikes from diverse directions. Furthermore, when being placed in the humanoid robot's head, it can monitor continuous motions like left-kicking, bending knees, standing on one leg and doing the splits. Such a single inertial sensor provides a building block for motion monitoring of humanoid robots and for future development of robotics. Graphical Abstract: ga1 Highlights: Self-powered magnetoelectric sensors for robot motion monitoring was proposed. Detection precision down to 0.06 m/s 2 for acceleration and 2° for tilting angle. Accurately monitor head shaking and sudden strikes from diverse directions. Real-time perception for complex continuous movements such as left-kicking.